2022
DOI: 10.1111/jdi.13740
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding ribonucleic acid ATP2B1‐AS1 modulates endothelial permeability through regulating the miR‐4729–IQGAP2 axis in diabetic retinopathy

Abstract: Aims/Introduction: Mounting evidence shows that long non-coding RNAs (lncRNAs) are important to modulate the biological process of diabetic retinopathy (DR). We aimed to investigate the role of lncRNAs in DR and elucidate the exact mechanism. Materials and Methods: Real-time quantitative polymerase chain reaction was carried out to distinguish the lncRNA ATPase plasma membrane Ca 2+ transporting 1 antisense RNA 1 (ATP2B1-AS1) expression in DR patients and HG-treated human retinal endothelial cells (HRECs). Dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…ATP2B1-AS1, also known as intergenic long non-protein-coding RNA 936 (LINC00936), is underexpressed in various diseases. Ren and colleagues assessed patients with diabetic retinopathy and learned that down-regulation of ATP2B1-AS1 expression could ameliorate cell permeability by targeting miR-4729, thereby alleviating retinopathy in patients [ 9 ]. Shu et al stated that LINC00936 was downregulated in ovarian cancer tissues and that the combination of miR-221-3p with high expression of LINC00936 controlled the occurrence of ovarian cancer [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATP2B1-AS1, also known as intergenic long non-protein-coding RNA 936 (LINC00936), is underexpressed in various diseases. Ren and colleagues assessed patients with diabetic retinopathy and learned that down-regulation of ATP2B1-AS1 expression could ameliorate cell permeability by targeting miR-4729, thereby alleviating retinopathy in patients [ 9 ]. Shu et al stated that LINC00936 was downregulated in ovarian cancer tissues and that the combination of miR-221-3p with high expression of LINC00936 controlled the occurrence of ovarian cancer [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA ATP2B1-AS1 (ATP2B1-AS1) is a 3,626 bp transhipment antisense RNA, located at CHR12:89,708,954 − 89,713,726 [ 8 ]. In recent decades, ATP2B1-AS1 has been reported to play regulatory and control functions in many diseases, suggesting that ATP2B1-AS1 may participate in disease progression [ 8 , 9 ]. What’s more, a variety of LUAD-related lncRNAs have been confirmed to be involved in the treatment process and survival outcomes of patients, such as SATB2-AS1, BFSP2-AS1, LINC01089 and GAS6-AS1 [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that ATP2B1-AS1 acts as a miR-4729 sponge to regulate the expression of IQGAP2, reducing high-glucose-induced endothelial dysfunction in DR. This phenomenon has tumor suppressive effects in many cancers, controlling endothelial cells dysfunction ( 31 ). Our study identified 20 upregulated, and two downregulated lncRNAs from obese samples before and after receiving LSG treatment; a lncRNA–miRNA–mRNA ceRNA network was constructed with one lncRNA, ten miRNAs, and three biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other lncRNAs have been shown to be downregulated in different contexts related to the DR ( Table 2 ), but more investigations are still needed. In particular, low expression of AK077216 , Ribosomal Protein SA Pseudogene 52 ( RPSAP52 ) and ATP2B1 Antisense RNA 1 ( ATP2B1-AS1 ) has been observed in patients with DR [ 167 , 168 , 169 ]. Interestingly, the over-expression of AK077216 and RPSAP52 in HG-induced ARPE-19 and RPE cells, respectively, inhibits cellular apoptosis [ 167 , 168 ].…”
Section: Long Non-coding Rnas With Reduced Expression In Diabetic Ret...mentioning
confidence: 99%
“…The former was reported as able to downregulate miR-383 [ 167 ], the latter as able to interact with miR-365, that in turn reduces the expression of Tissue Inhibitor of MetalloProteinases-3 ( TIMP3 ) gene [ 168 ]. Moreover, it has been reported that ATP2B1-AS1 over-expression in HRECs significantly reduces cell proliferation, migration, permeability, and angiogenesis induced by HG conditions, possibly by sponging miR-4729 and regulating the IQ motif-containing GTPase-activating protein 2 (IQGAP2) [ 169 ]. Furthermore, diabetic (vs. non-diabetic) mice display reduced expression of SOX2 Overlapping Transcript ( SOX2OT ) [ 170 ].…”
Section: Long Non-coding Rnas With Reduced Expression In Diabetic Ret...mentioning
confidence: 99%